Surgical outcomes following laparoscopic major hepatectomy for various liver diseases. Issue 43 (October 2016) - Kang, Sung-Hwa; Kim, Ki-Hun; Shin, Min-Ho; Yoon, Young-In; Kim, Wan-Jun; Jung, Dong-Hwan; Park, Gil-Chun; Ha, Tae-Yong; Lee, Sung-Gyu
Abstract : Abstract: The aim of the study was to report surgical outcomes (efficacy and safety) of laparoscopic major hepatectomy for various liver diseases. Although the number of laparoscopic liver resections has increased, expansion of laparoscopic major hepatic resection remains limited, mainly owing to the technical difficulties for the procedure as compared to open surgery. We describe our experiences with laparoscopic major hepatectomy for various liver diseases. We retrospectively reviewed the medical records of 192 patients who underwent laparoscopic major hepatectomy between October 2007 and March 2015 at Asan Medical Center, Korea. The mean age of the patients was 54 ± 11.6 years, and their mean body mass index was 23.5 kg/m 2 . The most common preoperative diagnosis was hepatocellular carcinoma (n = 82, 42.7%), followed by intrahepatic duct stones (n = 51, 26.6%). We performed 108 left hepatectomies, 55 right hepatectomies, 18 right posterior sectionectomies, 6 right anterior sectionectomies, 2 central bisectionectomies, and 3 donor right hepatectomies. The conversion rate was 1.6% (3 cases) due to bleeding, bile leakage, and uncontrolled hypercapnea during the operation. The mean operation time was 272 ± 80.2 minutes, and the mean estimated blood loss was 300.4 ± 252.2 mL. The mean postoperative hospital stay was 9.8 days. All resection margins were tumor-free in cases of malignant tumors. The morbidity rate was 3.1% (n = 6), including for case of biliary stricture. There were no deaths. Laparoscopic major hepatectomy, including donor hepatectomy, is a safe and feasible option for various liver diseases when careful selection criteria are used by a surgeon experienced with the relevant surgical techniques.